Effect of different cavity conditioners on microleakage of glass ionomer cement with a high viscosity in primary teeth - Mazaheri, Romina (Dent Res J (Isfahan), 2015)
BACKGROUND: Glass ionomer cement is a common material used in pediatric dentistry. The aim of this study was to evaluate the microleakage of high-viscosity glass ionomer restorations in deciduous teeth after conditioning with four different conditioners. MATERIALS AND METHODS: Fifty intact primary canines were collected. Standard Class V cavities (2 mm × 1.5 mm × 3 mm) were prepared by one operator on all buccal tooth surfaces, including both enamel and dentin. The samples were divided into five groups with different conditioners (no conditioner, 20% acrylic acid, 35% phosphoric acid, 12% citric acid, and 17% ethylenediaminetetraacetic acid [EDTA]). Two-way — ANOVA, Kruskal–Wallis and Mann–Whitney tests were used to compare the means of microleakage between the five groups. The significance level was set at P < 0.05. RESULTS: There was no significant difference between the means of microleakage in incisal (enamel) and gingival (dentin) margins (P = 0.34). Furthermore, there was no significant difference between the means of microleakage in enamel and dentin margins (P = 0.4). There was a significant difference between the means of microleakage in different groups (P = 0.03). CONCLUSION: Within the limitations of this study, it is suggested that 20% acrylic acid and 17% EDTA be used for cavity conditioning which can result in better chemical and micromechanical adhesion.